2003
DOI: 10.1074/jbc.m306470200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pathways of Nonhomologous End Joining That Are Differentially Regulated by DNA-dependent Protein Kinase-mediated Phosphorylation

Abstract: Nonhomologous end joining is the most common mechanism of DNA double-strand break repair in human cells. Here we show that nonhomologous end joining can occur by two biochemically distinct pathways. One requires a fraction containing the Mre11-Rad50-NBS1 complex. The other requires a fraction containing a novel, ϳ200-kDa factor that does not correspond to any of the previously described double-strand break repair proteins. The two pathways converge, sharing a common requirement for the DNA ligase IV-XRCC4 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 36 publications
7
47
0
Order By: Relevance
“…Dynan and colleagues (20) and Iliakis and colleagues (37) used in vitro end joining systems to demonstrate that kinase inactive DNA-PKcs can inhibit DNA-PKcsindependent subpathway(s) of NHEJ. Additionally, several reports using cellular systems have shown that inactivating DNAPKcs (by kinase inhibitors) blocks other DNA repair and metabolism pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dynan and colleagues (20) and Iliakis and colleagues (37) used in vitro end joining systems to demonstrate that kinase inactive DNA-PKcs can inhibit DNA-PKcsindependent subpathway(s) of NHEJ. Additionally, several reports using cellular systems have shown that inactivating DNAPKcs (by kinase inhibitors) blocks other DNA repair and metabolism pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas full-length DNA-PKcs efficiently complements both the coding joint and more modest signal joint deficit of the V3 cell line, neither isoform II nor III supported either coding or signal end joining. DNA-PKcs independent subpathway(s) of NHEJ have been reported (20). Residual signal end joining in DNA-PKcs deficient cells (dependent on Ku, XRCC4, and DNA ligase IV) may represent such a pathway.…”
Section: Dna-pkcs Isoforms II and Iii Do Not Complement The Nhej Defimentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of a substrate containing histone H1 has provided the first demonstration of DNA-PK-dependent endjoining reconstituted by using purified or in-vitro-expressed proteins. In contrast, NHEJ activity by partially purified cell-free extracts has been shown to require DNA-PK activity in a reaction that uses naked DNA as a substrate (8,37), and DNA-PK has been shown to be required for LX-mediated ligation in the presence of a partially purified factor of Ϸ200 kDa (8). Interestingly, we have observed that addition of naked DNA to cell-free extracts prepared under conditions that support NHEJ results in the binding of histone H1 to DNA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Although DNA-PK phosphorylation is required for the hairpin cleavage activity of Artemis and the biochemical activities of the DNA-PK and LX complexes have been established in vitro, little is known about the role of DNA-PK in DSB rejoining or its in vivo phosphorylation targets. Current models suggest that DNA-PK may regulate NHEJ (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%